Genome-Wide Study of Plant-Specific PLATZ Transcription Factors and Functional Analysis of OsPLATZ1 in Regulating Caryopsis Development of Rice (Oryza sativa L.) - Tao Yang; Xin-Tong Xu; Li-Jun Tang; Wen-Tao Wei; Yuan-Yuan Zhao; Jin-Xin Liu; Xue-Feng Yao; Heng Zhao; Chun-Ming Liu; Ai-Ning Bai (Plants)
Plant A/T-rich sequence- and zinc-binding protein (PLATZ) is a type of plant-specific zinc-dependent DNA-binding protein that binds to A/T-rich DNA sequences. This family is essential for plant growth, development, and stress response. In this study, 15 OsPLATZs were identified in the rice genome with complete PLATZ-conserved domains by CD-search, similar to those found in angiosperms. Multi-species phylogenetic analysis showed that PLATZs were conserved in photosynthetic organisms, and an evolutionary branch unique to angiosperms was identified among members of the PLATZ family. Fifteen OsPLATZs were represented by five groups, each with distinct characteristics. An analysis of protein structures and sequence motifs showed that OsPLATZs were similar within groups, but varied between them. The expression profile and qRT-PCR results showed that OsPLATZs had distinct expression patterns in different tissues, with some responding to stress induction. Most of the OsPLATZs localized to the nuclei, and were predicted to bind to DNA sequences by AlphaFold3, suggesting that they likely function as conventional transcription factors. We also identified OsPLATZ1, a caryopsis-specific gene that regulates grain filling and caryopsis development in rice. This research lays the foundation for exploring the structural diversity, evolutionary traits, expression profile, and possible roles of PLATZ transcription factors in rice.